Rapid and Sensitive Detection of Tomato Brown Rugose Fruit Virus in Tomato and Pepper Seeds by Reverse Transcription Loop-Mediated Isothermal Amplification Assays (Real Time and Visual) and Comparison With RT-PCR End-Point and RT-qPCR Methods - Rizzo, Domenico; Da Lio, Daniele; Panattoni, Alessandra; Salemi, Chiara; Cappellini, Giovanni; Bartolini, Linda; Parrella, Giuseppe (Frontiers in Microbiology, 2021)
Tomato brown rugose fruit virus (ToBRFV) represents an emerging viral threat to the productivity of tomato and pepper protected cultivation worldwide. The standard molecular methods for lab-based diagnosis of ToBRFV are reverse transcription-end point polymerase chain reaction (RT-PCR) or reverse transcription-quantitative polymerase chain reaction (RT-qPCR). These methods, however, are costly and require specific lab equipment and expertise, which severely limits their use in resource-poor diagnostic laboratories and their application to a large number of samples, as in the case of surveillance programs with the aim to avoid the introduction of the virus into new areas. In this paper, we develop and validate a one-step reverse transcription LAMP (RT-LAMP) platform for the detection of ToBRFV in tomato and pepper, both by visual screening and in real time. Moreover, these methods can also be applied successfully for virus detection in tomato and pepper seeds, which are suspected to be the principal vector for the long-distance dissemination of ToBRFV. The diagnostic specificity and sensitivity of both Real-Time LAMP and Visual LAMP are both 100%, with a detection limit of nearly 2.25 fg/L, showing the same sensitivity as RT-qPCR Sybr Green, but being at least 100 times more sensitive than RT-PCR diagnostic methods. In artificially contaminated seeds, the proposed LAMP assays detected ToBRFV in 100% of contaminated seed lots, for up to 0.025% and 0.033% contamination rates in tomato and pepper, respectively. Our results demonstrate that the proposed LAMP assays are simple, inexpensive, and sensitive enough for the detection of ToBRFV, especially in seed health testing. Hence, these methods have great potential application in the routine detection of ToBRFV, both in seeds and plants, reducing the risk of epidemics.